Canadian Cohort Obstructive Lung Disease (CanCOLD): Fulfilling the Need for Longitudinal Observational Studies in COPD. (1st April 2014) - Bourbeau, Jean; Tan, Wan C.; Benedetti, Andrea; Aaron, Shawn D.; Chapman, Kenneth R.; Coxson, Harvey O.; Cowie, Robert; Fitzgerald, Mark; Goldstein, Roger; Hernandez, Paul; Leipsic, Jonathon; Maltais, Francois; et al.
Abstract: Awareness, diagnosis and treatment of COPD, compared to other major causes of death, remains far too low. This article describes the protocol objectives, design and the approaches taken in the Canadian Chronic Obstructive Lung Disease (CanCOLD) study, an epidemiological and integrated research. The CanCOLD study aims at better understanding heterogeneity of COPD presentation and disease progression. We hypothesize that individuals with unfavourable COPD "phenotypes" and subjects at-risk (ever smokers) with unhealthy lifestyle habits, environmental/work exposure, or co-morbidities will have increased risk of lung function decline independent of their cumulative exposure to cigarette smoke. The study is a prospective multi-center cohort study (9 sites in 6 provinces) built on the Canadian COPD prevalence study "COLD." The study plan is to include 1800 subjects at least 40 years old who were sampled from the general population and who were found to fall within 4 groups: 1) COPD moderate–severe (GOLD 2–4); 2) COPD mild (GOLD 1); 3) subjects at-risk (ever smoker); and, 4) subjects never-smoker free of airflow obstruction. Data collection is based on using strictly standardized methods involving questionnaires, pulmonary function and cardiorespiratory exercise tests, CT scans, and blood sampling. CanCOLD is a unique study that will address challenging and important research questions on COPD disease evolution and disease management and will help to define the natural history of COPD disease evolution in individuals at-risk for COPD and in those with COPD who have mild disease.